Down myeloid disorders: a paradigm for childhood preleukaemia and leukaemia and insights into normal megakaryopoiesis. - Vyas, P; Roberts, I (2006)
Newborns and children with Down Syndrome are predisposed to a range of blood disorders, which include acute lymphoblastic leukaemia and acute megakaryocytic leukaemia (AMKL). Over the last four years there has been considerable progress in our understanding of DS AMKL. Like other childhood leukaemias DS AMKL is initiated in utero and can present in the neonatal period as a clinically overt preleukaemic condition, transient myeloproliferative disorder (TMD). In addition to trisomy 21, fetal haemopoietic progenitors acquire N-terminal truncating mutations in the key megakaryocyte-erythroid transcription factor GATA1. These are the minimum required events for TMD to develop. In approximately 30% of TMD patients, additional as yet unidentified (epi)genetic mutations are required for progression to AMKL. Thus, DS TMD and AMKL provide a unique model of childhood leukaemia where the preleukaemic and leukaemic phases are ascertainable and separable allowing distinct steps in leukaemogenesis to be studied individually. These findings also have implications for the clinical management of DS TMD and AMKL specifically and also of childhood leukaemia more generally.